Unique role of admission hyperglycemia on myocardial infarction size and area at risk following an acute ST-elevation myocardial infarction - Taghreed Sayed Meshref; Mahmoud Aly Ashry; Refaat Fathi Abd El-Aal; Hisham Mostafa Imam; Dina Ali Hamad (SpringerOpen, 2020)
Abstract Background Hyperglycemia can adversely affect patients with acute ST-elevation myocardial infarction (STEMI) in both diabetic and non-diabetic patients. The majority of the studies had investigated the impact of admission hyperglycemia (AH) on cardiovascular morbidity and mortality while, in ours, we entailed its impact on final infarction size (FIS) and more interestingly, on the area at risk (AAR), both were estimated by cardiac magnetic resonance (CMR) imaging. Results AH showed significant positive correlations to FIS and AAR. Moreover, AH group had higher summation of ST segment elevation (sum STE), more maximum ST segment elevation (max STE), higher echocardiographic wall motion score index (WMSI), higher CMR estimated WMSI, and lower segmental ejection fraction (EF). Multivariate analysis showed that AH was independently associated with increased FIS. Conclusion Current study showed an association between AH and large FIS in STEMI patients.